Aberrant Origin of Radial Artery in Arm - Sathe, Vivek; Pokhrel, Rishi (Medical Journal of Shree Birendra Hospital, 2016)
During dissection in middle-aged male cadaver, an aberrant radial artery was noticed in the left arm. The artery was taking origin from the upper part of the brachial artery i.e. at a point when axillary artery leaves the axilla and becomes brachial artery. Course of the aberrant vessel was studied in the arm and the forearm. In the upper part of arm the vessel took origin on the lateral side of brachial plexus trunks and traveled to the lateral region of the cubital fossa travelling lateral to the biceps brachii and deep to skin, superficial and deep fascia. In the lower part of the arm i.e. just above the cubital fossa, aberrant vessel was lateral and entered the forearm deep to the pronator teres. Throughout its course the vessel laid superficial to forearm muscles, it was covered by the skin superficial and deep fascia. At the wrist its position was normal i.e. against anterior border of the radius.